2006
DOI: 10.1111/j.1600-6143.2006.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Allograft Injury Is Associated with Urinary Tract Infection Caused by Escherichia coli Bearing Adherence Factors

Abstract: Urinary tract infections are the most common infection in renal transplant patients and Escherichia coli (E. coli) is the most common clinical isolate. Although acute allograft injury (AAI) secondary to urinary tract infection (UTI) has been reported, the incidence of AAI associated with UTI, the virulence factors express by uropathic E. coli and whether virulence factors are associated with renal allograft outcome have not been described. We collected E. coli from our renal transplant patients with UTI, deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 60 publications
(67 reference statements)
4
53
2
1
Order By: Relevance
“…Our prevalence of 27% of papGII in PN is not high if compared with other studies that reported rates of 54% to 93% in the non-Tx population (5,11,12,15). In Tx patients, Rice et al (21) found significant differences regarding the papGII prevalence between PN and lower UTIs-47% versus 18%. Nevertheless, in experimental models, Mobley et al (42) have shown that adherence mediated by the P-fimbrial adhesin played only a subtle role in the development of PN.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…Our prevalence of 27% of papGII in PN is not high if compared with other studies that reported rates of 54% to 93% in the non-Tx population (5,11,12,15). In Tx patients, Rice et al (21) found significant differences regarding the papGII prevalence between PN and lower UTIs-47% versus 18%. Nevertheless, in experimental models, Mobley et al (42) have shown that adherence mediated by the P-fimbrial adhesin played only a subtle role in the development of PN.…”
Section: Discussioncontrasting
confidence: 39%
“…Thus, the lack of papGIII in E. coli strains was an independent factor associated with PN in all patients (OR ϭ 4.88) and Tx patients (OR ϭ 5.07). On the other hand, some studies did not find any association between papGIII and PN in non-Tx (5,11,13,15) or Tx patients (21), with the prevalence ranging from 4% to 35%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute pyelonephritis can also contribute to chronic allograft dysfunction by direct kidney injury, as shown in a study in which multiple focal scarring defects were observed by technetium Tc 99m dimercaptosuccinic acid single photon emission computed tomography, or 99m Tc-DMSA SPECT, in kidney transplant recipients with recurrent late UTI. Acute allograft injury was observed only in patients with infection with uropathogenic E coli that expressed virulence factors such as P fimbriae but not with infection by other strains (174).…”
Section: Bacterial Respiratory Tract Infectionmentioning
confidence: 99%